Seismic and Energetic Interventions on a Typical South Italy Residential Building: Cost Analysis and Tax Detraction - Formisano, Antonio; Vaiano, Generoso; Fabbrocino, Francesco (Frontiers in Built Environment, 2019)
Italian buildings are mainly represented by unreinforced masonry constructions, which were mostly built before 1970, often without respecting seismic design criteria. The main objective of Italian designers is, therefore, to retrofit these buildings in order to improve their safety under earthquake, as well as to preserve the memory of the ancient building art. In addition, the assessment of the building energetic efficiency is nowadays a very pressing need for designers and practitioners. Energetic efficiency represents the capacity to optimize the consumption of energy resources in order to reach prefixed requirements for the environment protection. This paper shows both seismic and energetic retrofitting interventions on a residential unreinforced masonry building typical of the constructive practice in the South Italy. Initially, the building characterization under geometrical and structural viewpoints is done. Subsequently, the seismic vulnerability verification is performed with unsatisfactory results, so requiring upgrading or retrofitting interventions. Moreover, with the aim to increase living comfort and energy efficiency, energetic upgrading interventions, aimed at decreasing the building transmittance, are proposed. Seismic and energetic interventions are then computed from the economic point of view in order to evaluate the financial contributions foreseen by the Italian 2018 Balance Law through the Sismabonus and Ecobonus tools, respectively. Finally, the study proposes a global performance index able to take into account contemporary the seismic, energetic and economic benefits deriving from retrofitting interventions applied on the inspected residential building.